The caregiver role in thromboprophylaxis management in atrial fibrillation: A literature review. (1st April 2015) - Ferguson, Caleb; Inglis, Sally C; Newton, Phillip J; Middleton, Sandy; Macdonald, Peter S; Davidson, Patricia M
Abstract: Background: Atrial fibrillation is a common arrhythmia and a risk factor for adverse events including stroke. People living with atrial fibrillation are commonly elderly and have multiple comorbidities. The role of a caregiver in supporting the individual to manage a chronic and complex condition has received limited attention. Objectives: This review aims to summarize available information on the caregiver role in atrial fibrillation, specifically in promoting adherence to thromboprophylaxis and evidence for strategies to support and enable the caregiver. Data sources: A review of electronic databases and search engines was undertaken including Medline, Scopus and CINAHL. The search terms 'atrial fibrillation', 'anticoagulation', 'carer', 'caregiver', 'family support' were used. Dates searched were from January 1990 to November 2012. Results: The review found limited original clinical research studies. The majority of the literature identified in the initial search included review papers and work which recommends the inclusion of the caregiver in the care of patients with atrial fibrillation but limited empirical evidence. Conclusions: Caregivers have an essential role to play in advocacy, family centred care and shared decision-making. This may influence thromboprophylaxis treatment choices and potentially adherence. Assessment of caregiver needs and support should be central to patient assessment and care planning. There is a need for clinical intervention studies which more target and address the caregiver role.